2010
DOI: 10.1152/ajpendo.00693.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone alters cyclooxygenase-2 levels in human coronary artery smooth muscle cells

Abstract: Osterlund KL, Handa RJ, Gonzales RJ. Dihydrotestosterone alters cyclooxygenase-2 levels in human coronary artery smooth muscle cells. Am J Physiol Endocrinol Metab 298: E838 -E845, 2010. First published January 26, 2010; doi:10.1152/ajpendo.00693.2009.-Both protective and nonprotective effects of androgens on the cardiovascular system have been reported. Our previous studies show that the potent androgen receptor (AR) agonist dihydrotestosterone (DHT) increases levels of the vascular inflammatory mediator cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 38 publications
4
52
0
Order By: Relevance
“…COX-2 membranes were not stripped between anti-COX-2 and GAPDH incubations. COX-2 antibody specificity was verified with LPS-stimulated RAW 264.7 mouse macrophage cell lysate (Santa Cruz Biotechnology, Santa Cruz, CA) in a previous study (18). COX-1 antibody specificity was verified using human coronary vascular smooth muscle lysate [ Fig.…”
Section: Subjectsmentioning
confidence: 95%
See 1 more Smart Citation
“…COX-2 membranes were not stripped between anti-COX-2 and GAPDH incubations. COX-2 antibody specificity was verified with LPS-stimulated RAW 264.7 mouse macrophage cell lysate (Santa Cruz Biotechnology, Santa Cruz, CA) in a previous study (18). COX-1 antibody specificity was verified using human coronary vascular smooth muscle lysate [ Fig.…”
Section: Subjectsmentioning
confidence: 95%
“…An aliquot of the homogenized sample that was used to determine the levels of COX-1 and COX-2 protein was also examined using standard immunoblotting methods (18). Human muscle samples were homogenized as described above.…”
Section: Subjectsmentioning
confidence: 99%
“…Interestingly, under normal conditions without proinflammatory stimulation, DHT alone increased COX2 levels compared with the vehicle and AR antagonism attenuated the response. The authors suggest that DHT differentially effects COX2 levels under physiological and pathophysiological conditions in human coronary artery smooth muscle cells and via AR-dependent andindependent mechanisms influenced by the physiological state of the cell (Osterlund et al 2010). DHT was also shown to suppress hypoxia-induced upregulation of COX2 by inhibiting hypoxia-inducible factor 1a (HIF1a (HIF1A)) DNA binding and subsequent transcription of the COX2 gene in primary human brain VSMCs (Zuloaga & Gonzales 2011).…”
Section: Ar-and Er-independent Mechanismsmentioning
confidence: 98%
“…Using the non-aromatisable androgen DHT, Osterlund et al (2010) demonstrated that human coronary artery smooth muscle cells (HCASMCs) attenuate their increased expression of the inflammatory mediator COX2 under inflammatory conditions (LPS or IL1b) when co-treated with DHT. This effect of DHT was not altered by AR antagonism with bicalutamide.…”
Section: Ar-and Er-independent Mechanismsmentioning
confidence: 99%
“…COX2 expression is upregulated in response to DHT in periovulatory granulosa cells, where androgens were found to directly regulate the COX2 gene through an AR-dependent mechanism [60]. Within the vasculature, DHT increases COX2 expression in human coronary artery smooth muscle cells and, while not measured directly, that study suggested that DHT might lead to increased prostacyclin levels [61]. Consistent with that suggestion, testosterone leads to an enhanced vasodilatory response in diabetic rabbits compared with control animals and occurs, in part, due to increased COX2-derived prostacyclin synthesis [62].…”
Section: Discussionmentioning
confidence: 95%